Standing alongside your friends: Network centrality and providing troops to UN peacekeeping operations. (May 2016) - Ward, Hugh; Dorussen, Han
Why do countries contribute troops to UN peacekeeping? Recognizing the incentives to free ride on the contributions of other countries, existing explanations have tended to focus on the private benefits of providing troops. There has been particular emphasis on some major contributing countries that gain financially from providing peacekeepers. An alternative explanation could be that countries prefer to deploy troops to peacekeeping alongside countries with similar foreign policy preferences in order to maximize jointly produced private benefits. Accordingly, the willingness to provide peacekeepers should depend on which other countries are providing troops to peacekeeping operations. The implications are explored within the context of games on networks, and it is demonstrated that in equilibrium countries that are more Bonacich central in the network of foreign policy preference contribute disproportionally to UN peacekeeping. Based on actual contributions to UN peacekeeping from 1990 until 2011, we find that policy complementarities explain why countries provide a larger proportion of peacekeepers to a particular mission. Importantly, centrality in the network of policy complementarities matters and not simply that countries have moderate policy preferences. There is robust evidence for the prevalence of peacekeeping alongside your 'friends'; in effect, countries with a lot of 'friends' contribute more peacekeepers.